(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: The incidence of ovarian cysts in pregnancy is postulated to be approximately 3%. Most of these cysts are benign, with 6% of them being benign. Most of these masses are diagnosed incidentally during routine ultrasound. The most common are functional cysts. Most of these cysts do not have symptoms and are managed conservatively. For persistent symptomatic cysts, medical and surgical management is a viable option. Case series: We present cases of three patients, two of whom were managed conservatively. One of the patients with a corpus luteum cyst was managed surgically and did well, whereas the other two patients were noted to have asymptomatic dermoid cysts. Pregnancy outcomes for the two who delivered were unaffected, including their modes of delivery. Conclusion: Adnexal masses are common during pregnancy. There is a need to evaluate and characterize these masses even during pregnancy. Management options for adnexal masses are primarily conservative, but for masses that meet the criteria for surgical management, surgery is safe, especially in the second trimester. A laparoscopic approach for abdominal surgery in the second trimester is feasible and relatively safe, as demonstrated in the present case. Modification of entry and surgical approaches and preoperative planning are important when considering surgery during pregnancy. Relief of pain symptoms during pregnancy will lead to a positive pregnancy experience.